Drainage System in Humanist Open Space Lunggi Park, Sambas City - Sasmita, Dwi Fitri; Nurhayati, Nurhayati; Andy, Uray Ferry (Semarang State University, 2020)
Abstract. A humanist open space area will not be implemented if it leaves some important segments in society such as parents, children, women and people with special needs. Integration of green infrastructure is needed to optimize open space area values. Public facilities and infrastructure especially for people with disabilities must meet four principles and criteria which include easiness, usefulness, safety and independence. Lunggi Park is one of the open space areas that still not accessible for all people. Drainage channel have a huge role in controlling water runoff in Lunggi Park. The research is concentrated in designing drainage system for Lunggi Park in order to construct a suited facilities and infrastructure for parents, children, women and people with special needs. This research also uses hydrological and hydraulic analysis in collecting prime and secondary data. The highest rainfall in 2008 was 192 mm. The processing of rainfall data using Gumbel Type I Method obtained a maximum discharge of a 2-year return period of 0,0445, a 5-year return period of 0,0569, a 10-year return period of 0,0649, a 20 year return period of 0,0728 and for a 25 year return period of 0,0744. Based on this result, the facilities and infrastructure of Lunggi Park should be arranged. The channels that do not function optimally is in spot one, two and four, so it is necessary to arrange new dimensions for these spots. Channel in spot one is designed to be square with 1,10 meters wide and 0,91 meters high. Channel in spot two is designed to be square with 1,40 meters wide and 0,76 meters high. Channel in spot four is designed to be square with 1,55 meters wide and 0,68 meters high.